2019
DOI: 10.1111/dewb.12239
|View full text |Cite
|
Sign up to set email alerts
|

Cultural considerations in forgoing enteral feeding: A comparison between the Hong Kong Chinese, North American, and Malaysian Islamic patients with advanced dementia at the end‐of‐life

Abstract: Cultural competence, a clinical skill to recognise patients' cultural and religious beliefs, is an integral element in patient‐centred medical practice. In the area of death and dying, physicians' understanding of patients' and families' values is essential for the delivery of culturally appropriate care. Dementia is a neurodegenerative condition marked by the decline of cognitive functions. When the condition progresses and deteriorates, patients with advanced dementia often have eating and swallowing problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Still, it remains unsettled in Malaysia and Hong Kong, which results in a lively debate in the class (Hudu et al 2016 ; So et al 2016 ). These examples demonstrated that there is no unified approach to ethical problems, and responses are the result of a complex mix of moral and value-related issues (Ngan et al 2020 ; Turner 2005 ). A study also discussed that incorporating cases that are relevant to the local medical systems helps cultivate bioethical responsiveness among the students (Bergstresser et al 2020 ).…”
Section: Common Challenges Encountered In Malaysia and Hong Kongmentioning
confidence: 99%
“…Still, it remains unsettled in Malaysia and Hong Kong, which results in a lively debate in the class (Hudu et al 2016 ; So et al 2016 ). These examples demonstrated that there is no unified approach to ethical problems, and responses are the result of a complex mix of moral and value-related issues (Ngan et al 2020 ; Turner 2005 ). A study also discussed that incorporating cases that are relevant to the local medical systems helps cultivate bioethical responsiveness among the students (Bergstresser et al 2020 ).…”
Section: Common Challenges Encountered In Malaysia and Hong Kongmentioning
confidence: 99%
“…In traditional Chinese culture, “feeding before hitting the road” is considered the most basic care for people who will die soon. For example, death-row prisoners typically have a full meal before execution, and starvation or dehydration is believed to be cruel punishment [ 24 ]. Chinese culture is deeply embedded in Taiwanese society.…”
Section: Discussionmentioning
confidence: 99%
“…Unique aspects of an individual's culture and the degree to which acculturation has taken place for that individual (interaction of two cultures; e.g., American and Mexican) can also play a role in decision making regarding approaches to dysphagia treatment (Mackie, 2001;Padilla et al, 2019). For example, feeding tube placement may be viewed differently depending upon one's culture and/or religious beliefs (Mackie, 2001;Ngan et al, 2019). Cultural aspects may influence quality of life and stigma in the presence of dysphagia, and is therefore an important part of the evaluation process and consideration in treatment planning for each patient (Padilla et al, 2019).…”
Section: Special Considerations In Dysphagia Management For Those With Neurodegenerative Conditionsmentioning
confidence: 99%